Analisis Makna Leksikal Pada Lirik Lagu “Pupus” Karya Dewa 19 - Siti Nabilah Nurrohmah (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research is entitled analysis of the lexical meaning of the song "PUPUS" by Dewa 19. This study aims to discuss the lexical meaning of a song lyric. Lexical meaning is the meaning of the smallest part of a word that has full meaning. Lexical meaning has an important role in language use because this meaning connects language, words and sentences that exist inside and outside the language. This lexical meaning cannot be changed or is already in the dictionary. In this study, the lyrics of the song become one of the determinations of the analysis of lexical meaning. This research uses a qualitative descriptive method, the data starts from the stage of reading and knowing the lyrics of the song to be analyzed in order to conclude the results of the research on the lexical meaning contained in the song "PUPUS" by Dewa 19.